LEFT MAIN CORONARY ARTERY STENTING - Khan, Muhammad Nadir; Muqaddas, Tahira (Pakistan Armed Forces Medical Journal, 2018)
Coronary artery bypass surgery is considered as the gold standard treatment of unprotected left main coronary artery (ULMCA) disease. Over the last 2 decades, improvement in stent technology and operators experience explained the increased number of reports on the results of percutaneous coronary interventions (PCIs) for the treatment of left main (LM) coronary artery lesion. The recent data which compared efficacy and safety of PCIsusing drug-eluting stent and coronary artery bypass surgery showed comparable results and a lesser need for repeat revascularization for coronary artery bypass surgery.